Love and Spirituality - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 1996)
What is the essence of the spiritual development of people? This is the question that is asked by philosophers, psychologists, educators and artists. The article describes different outlooks on love and spirituality – logotherapy, psychotherapeutic school, created by V. Frankl, as well as ideas of Lithuanian authors. A more detailed analysis of the concepts of S. Yla and P. Maldeikis is presented. The catholic view on love and spirituality is most vividly expressed in the works of K. Wojtyla. The final part of the article ends with the conclusion that the concepts of love presented by the authors mentioned above will provide the basis for further research in this field.
Keywords: Spirituality; love; Frankl's logotherapy; catholic view; K. J.Wojtyła.